The definition of placebo in the informed consent forms of clinical trials. - Astrid Hernández; Josep-E Baños; Cristina Llop; Magí Farré (PLoS ONE, 2014)
AIM: Lack of knowledge concerning the nature of placebo and why it is necessary may influence the participation of patients in clinical trials. The objective of the present study is to review how placebo is described in written information for participants in clinical trials to be evaluated by a Human Research Ethics Committee. METHODS: All research protocols submitted for evaluation in a Spanish hospital during 2007-2013 were reviewed. The main characteristics of the studies using a placebo were collected. Three authors read each of them to determine how the term "placebo" was explained and if there was any comment on its efficacy and safety. RESULTS: Two thousand seven-hundred and forty research protocols were evaluated, of which three hundred and fifty-nine used a placebo. Pharmaceutical companies sponsored most placebo-controlled clinical trials (91.9%), and phase III studies were the commonest (59.9%). Oncology (15.0%), cardiology (14.2%), and neurology (13.1%) made the greatest contributions. A review of the informed consent forms showed that placebo was described in a similar manner in most studies: the explanation was limited to between four and eight words. Very few gave information about the risks of its use or adverse reactions from its administration. None of the studies provided details about the placebo effect. And 23 lacked any information about placebo at all. CONCLUSIONS: Explanations about placebo in informed consent forms is often scarce, and information about the placebo effect and associated risks are absent. This situation may influence a full understanding of placebo by participants in clinical trials and might reduce their informed decision to participate.